Go Essentials: Concurrency, Connectivity, and High-Performance Apps. - Tebeka, Miki (linkedin.com, 2022)
Write more efficient, reliable applications with Go. Learn Go basics, including programming with Go basic types, structs and functions, concurrency, and networking.